2013
DOI: 10.5194/acp-13-165-2013
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between total ozone and atmospheric dynamics and chemistry at mid-latitudes – Part 2: The effects of the El Niño/Southern Oscillation, volcanic eruptions and contributions of atmospheric dynamics and chemistry to long-term total ozone changes

Abstract: Abstract. We present the first spatial analysis of "fingerprints" of the El Niño/Southern Oscillation (ENSO) and atmospheric aerosol load after major volcanic eruptions (El Chichón and Mt. Pinatubo) in extreme low and high (termed ELOs and EHOs, respectively) and mean values of total ozone for the northern and southern mid-latitudes (defined as the region between 30° and 60° north and south, respectively). Significant influence on ozone extremes was found for the warm ENSO phase in both hemispheres during spri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…Thirdly, we compare our analysis with the analysis of total ozone data in Rieder et al (2010) and Rieder et al (2013). Our AMM analysis finds a significant contribution of ENSO to Boulder (US) ozone variability for PC score 3 (where ozone is maximum), which is similar to the result of Rieder et al (2010) analysis that also found a positive contribution over the US region.…”
Section: Figsupporting
confidence: 73%
See 4 more Smart Citations
“…Thirdly, we compare our analysis with the analysis of total ozone data in Rieder et al (2010) and Rieder et al (2013). Our AMM analysis finds a significant contribution of ENSO to Boulder (US) ozone variability for PC score 3 (where ozone is maximum), which is similar to the result of Rieder et al (2010) analysis that also found a positive contribution over the US region.…”
Section: Figsupporting
confidence: 73%
“…Note that the contribution is significant only for Winter and Spring months. According to Rieder et al (2013), over Europe the total ozone analysis showed a negative effect of ENSO, but not significant, which is supported by our analysis of PC score 3 for Arosa that shows the non-significant influence. Rieder et al (2013) also indicated the seasonal difference in the ENSO contribution.…”
Section: Figsupporting
confidence: 65%
See 3 more Smart Citations